Small farm equipment for developing countries : (The international rice research institute, 1986)
The book gathers the papers presented at the conference “Small Farm Equipment for Developing Countries: Past Experiences and Future Priorities held at IRRI 2-7 September 1985. The papers share experiences in developing machines for small farmers and reviewed and evaluated the results.